PH-tuned diverse structures and properties: two Anderson-type polyoxometalate-based metal–organic complexes for selective photocatalysis and adsorption of organic dyes. Issue 112 (21st November 2016) - Wang, Xiuli; Sun, Junjun; Lin, Hongyan; Chang, Zhihan; Liu, Guocheng; Wang, Xiang
Abstract : Two novel Anderson-type POM-based metal–organic complexes were synthesized, which exhibit high selective photocatalytic activities for the degradation of organic dyes. Interestingly, 2 also shows selective adsorption capacity of organic dyes. Abstract : Two novel Anderson-type polyoxometalates (POMs)-based metal–organic complexes, namely, Cu5 (μ2 -OH)2 (4-dpye)2 [CrMo6 (OH)5 O19 ]2 (H2 O)10 (1 ), Cu(4-Hdpye)[CrMo6 (OH)6 O18 ](H2 O)2 ·2H2 O (2 ) (4-dpye = N, N ′-bis(4-pyridinecarboxamide)-1, 2-ethane), were hydrothermally synthesized in different pH ranges and structurally characterized by single-crystal X-ray diffraction, IR spectra, powder X-ray diffraction (PXRD) and thermogravimetric analyses (TGA). Complex1 shows a 3D (3, 4)-connected framework constructed by the 2D Cu5 (μ2 -OH)2 [CrMo6 (OH)5 O19 ]2 inorganic layer and bidentate 4-dpye bridging ligands. Complex2 exhibits a 2D polymeric structure based on the 2D Cu[CrMo6 (OH)6 O18 ](H2 O)2 layer and monodentate 4-Hdpye ligands. The complexes1 and2 prove that the pH value plays an important role not only in the synthesis and structures but also for the properties of the title complexes. Their electrochemical behaviour and electrocatalytic activities towards the reduction of bromate and hydrogen peroxide have been reported. In addition, the selective photocatalytic properties and adsorption of organic dyes for1 and2 have been investigated. Complex1 possesses good photocatalytic activity towards the degradation of organic dyes Congo Red (CR) and methylene blue (MB), while complex2 has high adsorption capacity of MB/CR at room temperature. All MB/CR molecules adsorbed on2 can be completely released in NaCl-containing DMF solution.